Alcohol-Related Liver Disease: Basic Mechanisms and Clinical Perspectives - Liu, Szu-Yi (Int J Mol Sci, 2021)
Alcohol-related liver disease (ALD) refers to the liver damage occurring due to excessive alcohol consumption and involves a broad spectrum of diseases that includes liver steatosis, steatohepatitis, hepatitis, cirrhosis, and hepatocellular carcinoma (HCC). The progression of ALD is mainly associated with the amount and duration of alcohol usage; however, it is also influenced by genetic, epigenetic, and environmental factors. The definite diagnosis of ALD is based on a liver biopsy, although several non-invasive diagnostic tools and serum biomarkers have emerging roles in the early detection of ALD. While alcohol abstinence and nutritional support remain the cornerstone of ALD treatment, growing evidence has revealed that the therapeutic agents that target oxidative stress or gut-liver axis, inflammatory response inhibition, and liver regeneration enhancement also play a role in ALD management. Furthermore, microRNAs modulation and mesenchymal stem cell-based therapy have emerging potential as ALD therapeutic options. This review summarizes the updated understanding of the pathophysiology, diagnosis, and novel therapeutic approaches for ALD.